Kualitas Air Tanah Sumur Gali Dangkal pada Batugamping Sentolo Daerah Balecatur Bagian Selatan, Kapanewon Gamping - Widiyaningsih, Harti; Erwin Wijaya, Andy (ReTII, 2024)
The research location is in the southern part of Balecatur Village, Kapanewon Gamping. This research aims to determine the quality of groundwater in shallow dug wells located in limestone lithology. The research method used is to use primary data through direct measurement observations in the field and sample testing in the laboratory as well as secondary data to see the quality of ground water in the research area. Based on the results of observations of visual physical descriptions and measurements in the field of color, taste, smell, temperature, pH, TDS at 6 well observation locations, the water generally shows that it is suitable, while based on the analysis of physical and chemical parameters in 2 samples with water quality standards for hygiene purposes and sanitation RI Minister of Health Regulation no. 2 of 2023, samples showed that dug well water had values ​​that exceeded the TDS standard (<300 mg/l) in all observed wells with values ​​between 408 – 601mg/l and color in the Sum-1 well. This TDS value exceeds the quality standard, it is possible for water to be in a well with limestone lithology, because the nature of limestone is easily soluble so that some minerals dissolve in water such as lime (calcium carbonate) and the condition of well water stored in the well for a long time is affected by rock weathering.